Theranostics in Interventional Oncology: Versatile Carriers for Diagnosis and Targeted Image-Guided Minimally Invasive Procedures - Degrauwe, Nils; Hocquelet, Arnaud; Digklia, Antonia; Schaefer, Niklaus; Denys, Alban; Duran, Rafael (Frontiers in Pharmacology, 2019)
We are continuously progressing in our understanding of cancer and other diseases and learned how they can be heterogeneous among patients. Therefore, there is an increasing need for accurate characterization of diseases at the molecular level. In parallel, medical imaging and image-guided therapies are rapidly developing fields with new interventions and procedures entering constantly in clinical practice. Theranostics, a relatively new branch of medicine, refers to procedures combining diagnosis and treatment, often based on patient and disease-specific features or molecular markers. Interventional oncology which is at the convergence point of diagnosis and treatment employs several methods related to theranostics to provide minimally-invasive procedures tailored to the patient characteristics. The aim is to develop more personalized procedures able to identify cancer cells, selectively reach and treat them, and to assess drug delivery and uptake in real-time in order to perform adjustments in the treatment being delivered based on obtained procedure feedback and ultimately predict response. Here, we review several interventional oncology procedures referring to the field of theranostics, and describe innovative methods that are under development as well as future directions in the field.